Memory and Identity: how societies construct and administer their past? - C. de Rezende Martins, Estevão (T.E.X.T.O.S DE H.I.S.T.Ó.R.I.A. Revista do Programa de Pós-graduação em História da UnB., 2012)
The main interest of the debate on memory and collective (social) identity is the historical one. The richness of the various continents the participants come from, with their complexity and differences, should permit our debate to take in account the variety not only of theEuropean experience (traditionally linking society, nation and state together),but specially those of the emerging, complex, multicultural societies outside Europe's as well.